SOCIAL NETWORKS AND DESTINATIONS OF CULTURAL TOURISM IN SERBIA - Surla, Tamara; Miljković, Jovana (The Business of Tourism, 2023)
Travel and tourism are the most promising industries in the world, and information is critical to their success. Social networks represent a significant source of information that can strongly influence tourist plans and the choice of tourist destinations. The use of social networks in tourism is growing rapidly, becoming an important marketing tool for tourism entrepreneurs. Serbia has great potential in the form of cultural tourism destinations, but so far it has not been investigated how social networks can influence the process of selecting these destinations. Therefore, the goal of the research was to explore the habits of social network usage among tourists visiting cultural tourism destinations in Serbia, as well as to find out which destinations are the most visited. In order to achieve this, a survey was conducted among 400 respondents who live in Serbia and use social networks. The results showed that respondents most often visit cities and old city centers, use social networks several times a day and that photos have the most significant influence when choosing a cultural tourism destination.